2002
DOI: 10.1021/la011499t
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Molecular Orientation in Solid Films via Self-Organization in the Liquid-Crystalline Phase

Abstract: We report the control of molecular orientation in solid films through self-organization and inducedorientation processes. We synthesized water-soluble cationic 3,4,9,10-perylene diimide (1) and studied its self-organization in aqueous solution. By UV-vis spectroscopy, H-aggregates of 1 were observed forming in solutions with concentrations as low as 10 -7 M. At concentrations above approximately 0.1 M (7% w/w), these solutions were observed with polarized microscopy to form a chromonic N phase (a nematic lyotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
94
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 51 publications
5
94
0
Order By: Relevance
“…1 5 However, the blueshifted absorption and excitation spectra that are observed suggest the C 12 -PDI+/PA complex is also aggregated in the ground-state (similarly to C 12 -PDI÷ alone). 36 Ground state aggregates have also been observed in related (but covalently linked) perylene diimides, based on NMR studies. 37 In the present materials, it is concluded that aggregation of the chromophores in the 7 presence of PA facilitates excimer formation by positioning the chromophores in closer proximity to each other.…”
Section: Bulk Spectroscopic Datamentioning
confidence: 98%
“…1 5 However, the blueshifted absorption and excitation spectra that are observed suggest the C 12 -PDI+/PA complex is also aggregated in the ground-state (similarly to C 12 -PDI÷ alone). 36 Ground state aggregates have also been observed in related (but covalently linked) perylene diimides, based on NMR studies. 37 In the present materials, it is concluded that aggregation of the chromophores in the 7 presence of PA facilitates excimer formation by positioning the chromophores in closer proximity to each other.…”
Section: Bulk Spectroscopic Datamentioning
confidence: 98%
“…[28,29] Functionalised dyes on self-assembly envisage greater utility, having multichromophores groups with novel optical and electronic properties. [30][31][32] In recent years, organic dyes have aroused interest due to improved colouring, fluorescence, adsorption and desorption performance. Thiacyanine dyes are one such example, [33,34] wherein the dyes are made up of two benzothiazole units coupled through conjugated double chains having two nitrogen centres with one atom positively charged.…”
Section: Introductionmentioning
confidence: 99%
“…Indanthrone is a polyaromatic dye that can be sulfonated to introduce hydrophilic sites on the disk periphery. In such compounds the polyaromatic faces remain hydrophobic, and this leads to extensive π-stacking in aqueous solution [8]. In indanthrone disulfonate solutions, this face-to-face stacking is extensive, leading to long rod-like aggregates of ~ 1.5 nm in diameter and about 300 nm in length (~ 200 aspect ratio) [9], while proton dissociation imparts negative charge that aids in aggregate dispersion (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This LC system is classified as lyotropic, since the rod alignment is induced by increase in concentration rather than decrease in temperature as in thermotropic liquid crystals. The same entropic forces cause rod alignment parallel to surfaces, as this configuration decreases the excluded volume at the LC/substrate interface [8,9]. The rod alignment is further improved when the solutions dry and the liquid crystalline order is converted to solid crystalline order in the deposited film.…”
Section: Introductionmentioning
confidence: 99%